Transformational leadership and flourishing in Portuguese professional firefighters: The moderating role of the frequency of intervention in rural fires - Maio, André; Chambel, Maria José; Carmona, Laura (Frontiers in Psychology, 2023)
Introduction The main objective of this study is to analyze the effect of transformational leadership on firefighters’ well-being and understand the moderating role of the frequency of intervention in rural fires in this relationship. Methods A total of 90 responses of Portuguese professional firefighters were analyzed in two waves (T1 and T2) separated by a period of 3 weeks during which the frequency of intervention in rural fires were also recorded on a daily basis. Results There is a direct and positive effect, albeit small, of the transformational leadership dimensions on flourishing. Moreover, the frequency of intervention in rural fires amplified the effect of individual consideration on this wellbeing indicator, and it was observed that the more frequent the firefighters intervene in rural fires, the stronger the effect of this leadership dimension on their flourishing. Discussion These results contribute to the literature to the extent that they highlight the role of transformational leadership in promoting well-being in high-risk professions, thus supporting the assumptions of the Conservation of Resources Theory (COR). Some practical implications are presented, as well as limitations and suggestions for future studies.